The Influence of “Rumah Pangan Kita” (RPK) Partnership on the Income of Grocery Traders in Malang - Az Zahra, Wara' Geffa; Dina Riana, Fitria; Haryati, Novi; Sujarwo, Sujarwo (FIA UB, 2025)
One of Perum Bulog's efforts to maintain price stability and food availability is distributing its products through the